Cytomorphological and Cytomorphometric Analysis of Oral Squames in Smokers Using Computer Aided Image Analysis System - Priyanka Choudhary; Jyoti Kasana; Bhupender Bhati; Vidyadevi Chandavarkar; Deepak Bhargava; Mithilesh N. Mishra (Journal of Pharmacy and Bioallied Sciences)
Objective: This study aimed to assess the impact of smoking on oral mucosa and evaluate the role of cytomorphometry in diagnosing and prognosing potentially malignant disorders. Study Design: The study included 75 patients both smokers and non-smokers with and without smoking-related lesions. We measured cellular diameter (CD), nuclear diameter (ND), cellular area (CA) and nuclear area (NA) of buccal mucosa squames using PAP stain and image analysis software (Pixel Pro by Labo Med). Results: Smokers, regardless of lesion presence showed increased ND, decreased CD, increased NA and decreased CA compared to non-smokers. ANOVA and t-tests indicated significant differences (P < 0.001). Conclusion: Exfoliative cytology proves to be a simple, fast and cost-effective method for screening potentially malignant disorders of the oral cavity.